1960
DOI: 10.1037/h0040551
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary knowledge and usage of schizophrenic subjects: A six-year follow-up.

Abstract: OR THE past 30 years vocabulary performance, used as a measure of former intelligence level, has played a prominent role in the assessment of intellectual deterioration. In recent years, however, the use of vocabulary measures in this manner has provoked a barrage of criticisms (see Yates, 1956, for a comprehensive review). Foremost among these criticisms, as they apply to deterioration in schizophrenics, has been the contention that vocabulary performance also is impaired in schizophrenics, and, hence, cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

1964
1964
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The available studies, however, provide conflicting results and have a variety of methodologic limitations (eg, small or nonrepresentative samples, no controls, brief follow-ups, and/or limited neuropsychological testing). 2,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Both neurodevelopmental and neurodegenerative views of neuropsychological deficits in schizophrenia seemingly remain viable. 10 While progression of deficit after illness onset clearly is not universal, or even typical of the disorder, a subset of persons with schizophrenia may evidence cognitive deterioration over time.…”
mentioning
confidence: 99%
“…The available studies, however, provide conflicting results and have a variety of methodologic limitations (eg, small or nonrepresentative samples, no controls, brief follow-ups, and/or limited neuropsychological testing). 2,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Both neurodevelopmental and neurodegenerative views of neuropsychological deficits in schizophrenia seemingly remain viable. 10 While progression of deficit after illness onset clearly is not universal, or even typical of the disorder, a subset of persons with schizophrenia may evidence cognitive deterioration over time.…”
mentioning
confidence: 99%
“…More importantly, the mean of this follow-up subsample in 1949 (14.4) was lower than that of the total group tested in 1949, i.e., the mean for the 170 subjects was 16.1 (Moran et al, 1952). In an earlier study of Veterans Administration patients, the 6-year follow-up subsample of 30 patients also had a lower mean vocabulary raw score in 1952 (21.8) than the total group (23.9), from which it was drawn (Moran et al, 1960). This does not indicate that the present findings of stability in vocabulary performance of schizophrenics apply only to low vocabulary subjects.…”
mentioning
confidence: 84%
“…The most obvious change in the 30 Veterans Administration patients studied earlier was an increased garrulousness (or decreased verbal facility) on second testing (Moran et-al., 1960). This was evident also in the 31 men in the present sample; the mean number of words used in their definitions increased from 88 to 118.…”
mentioning
confidence: 99%
“…et al (1969) found a normalization of associative performance in a sample of chronic schizophrenics after a follow-up period of 10 years. According to the literature (Yates, 1956;Moran et al, 1960;Wynne, 1963;Higgins et al, 1965), we should have expected some worsening or no change at all. A plausible cause for this discrepancy is that we used a longitudinal design, whereas the earlier studies (except for Moran et al, 1960) were cross-sectional.…”
mentioning
confidence: 99%
“…According to the literature (Yates, 1956;Moran et al, 1960;Wynne, 1963;Higgins et al, 1965), we should have expected some worsening or no change at all. A plausible cause for this discrepancy is that we used a longitudinal design, whereas the earlier studies (except for Moran et al, 1960) were cross-sectional. Because of its implications for the long-term prognosis in schizophrenia, it is important to establish the direction of an eventual change.…”
mentioning
confidence: 99%